The Great Communicator: Audrey Holland's Legacy and Lessons - Fromm, Davida; MacWhinney, Brian (Seminars in Speech and Language, 2024)
Audrey Holland's core beliefs of respect for people and the quality of their lives informed her life's work. This examination of the ways she managed the academic, research, and clinical parts of her illustrious career shows how Audrey leaves a rich legacy and serves as a model for navigating an impactful career path and enhancing clinical interactions. First, she mentored more than 30 doctoral students who then mentored further generations of students, ran clinics, or shaped policy. She also regularly taught classes, supervised student clinicians, and traveled the world doing lectures and workshops. Second, her scholarship spanned more than 50 years and a range of subjects, such as assessment and treatment, self-determination and self-advocacy, pragmatics, counseling, coaching, and communication strategies. Third, her collaborations with many colleagues within the field and in related fields extended her impact even further. Finally, a close analysis of her clinical communication style shows how Audrey's simple, nonverbal behaviors (e.g., eye contact, body position) brought out the best in the people with whom she worked. On all these levels—mentorship, scholarship, collaboration, and communication style—Audrey's legacy leaves a vast array of powerful lessons that can be studied, emulated, and appreciated for years to come.
Keywords: functional communication; person-centered approach; AphasiaBank; Famous People Protocol